Gestión de abastecimiento en la ferretería y automotriz chasi del Recinto Mata de Cacao. - Caballero Briones, Andrea Yaritza (2022)
The Hardware and Automotive Chasi is a private company with years of experience dedicated to retail sales of hardware and automotive materials, its objective is to know what is the supply process that the company currently has, in order to discover what is the level of performance that workers have when providing customer service. Through an exhaustive analysis that was carried out within the company, it was possible to determine that One of the problems for which there are shortcomings in the supply management of the Hardware and Automotive Chasi, is the lack of inventory control and an adequate billing system. , causing dissatisfaction and discomfort in customers for not knowing the existence of the product either inside the hardware store or in the warehouse, because it cannot be verified if it exists or not, generating poor customer service.